Replacing Soybean Meal with Hemp Leaves with Very Low THC Content in the Diet for Dairy Cows: Impact on Digestibility, Nitrogen Use Efficiency and Energy Metabolism - Jessica Schwerdtfeger; Solvig Görs; Björn Kuhla (Animals)
The aim was to investigate the suitability of Santhica 27 industrial hemp leaves as a protein source in dairy cow nutrition. Twelve Holstein dairy cows received a total mixed ration (TMR) containing 7.4% industrial hemp leaves (HEMP) and a TMR containing 3.5% soya extraction meal (CON) in a crossover design. Cows were kept in a free-stall barn for 2 weeks to measure feed intake, milk yield and sample plasma, ruminal fluid, and urine. In week 3, cows were housed in a respiration chamber to measure gas exchange, urine, and feces excretions. In the first two weeks, cows of the HEMP group rested longer but spent less time ruminating. Feeding the HEMP diet reduced dry matter intake (DMI), milk yield, and urinary N-metabolite concentrations and tended to lower total N-excretion, milk fat, and lactose concentrations. During the stay in the respiration chamber, DMI, milk yield, apparent digestibility, and crude protein degradability were similar between groups, but feeding the HEMP diet tended to reduce methane yield. In conclusion, Santhica 27 hemp leaves are a suitable protein source for dairy cows as they have no negative effects on animal health, apparent digestibility, and crude protein degradability. Nevertheless, inadequate adaptation to the diet reduces feed intake and milk yield.